PENGEMBANGAN MODUL DIGITAL MENGGUNAKAN FRAMEWORK TPACK UNTUK MENINGKATKAN KEMAMPUAN LIFE SKILLS SISWA - Marnita; Diding Nurdin; Eka Prihatin; Marwan (Postgraduate, University of Mataram, 2024)
The purpose of this study is to develop a digital module using the Technological Pedagogical Content Knowledge (TPACK) framework in enhancing students' life skills and assessing the effectiveness of lecturers' learning management. The respondents of this study were the fourth-semester students of the Primary School Teacher Education (PGSD) program. This study employed an R&D (Research and Development) design that follows the 4-D (Define, Design, Develop, and Disseminate) model. The design adopted the theory proposed by Plomp, which outlines five steps: problem analysis, design, realization, implementation, and evaluation. The findings of this study indicated that students have a significant role in teaching and learning process. It revealed the lecturers’ self-reflection on digital technology-based teaching abilities. Additionally, it implied the development of student creativity, critical thinking, collaboration, negotiation, and decision-making skills. These are integral components of 21st-century skills that play a pivotal role in students' future careers. This study concluded that the digital module using TPACK framework could enhance students' life skills and demonstrated high practicality regarding usage and lecturers’ self-development.